Optimization of energy tunnel heat extraction section design based on simulated annealing algorithm - LIU Jiaxin; HAN Chanjuan; CAI Guoqing (Shenzhen Daxue xuebao. Ligong ban)
Energy tunnel is an alternative energy-saving technology of ground source heat pump （GSHP）， which has been applied in China in recent years. However， the current engineering practice still lacks the mature design method， and the heat extraction section design of the energy tunnel usually depends on engineering analogy. It is necessary to develop a convenient and reliable method to assist energy tunnel design. To address this problem，an optimization framework is developed to guide the heat extraction section design of energy tunnel in the severe cold region based on numerical simulation and simulated annealing algorithm. With this framework， the location of the heat extraction section can be automatically selected based on the in-site geological and meteorological conditions. Then， sensitivity analysis in terms of different design parameters of the heat extraction section is conducted to investigate their influence on heat transfer efficiency and heat extraction section design. The results show that smaller pipe spacing， lower inlet water temperature， and higher flow rate of circulating medium in pipes will benefit the higher heat exchange efficiency， shorter design length of heat extraction section， and the resultant lower cost. In addition， the deviation of the starting position within several meters will not affect the total heat extraction capability for a certain length of the heat extraction section. The proposed methodology will provide important support for the energy tunnel design in engineering practice.